Pain and health-related quality of life with olaparib versus physician's choice of next-generation hormonal drug in patients with metastatic castration-resistant prostate cancer with homologous recombination repair gene alterations (PROfound): an open-label, randomised, phase 3 trial. Issue 3 (March 2022) - Thiery-Vuillemin, Antoine; de Bono, Johann; Hussain, Maha; Roubaud, Guilhem; Procopio, Giuseppe; Shore, Neal; Fizazi, Karim; dos Anjos, Gabriel; Gravis, Gwenaelle; Joung, Jae Young; Matsubara, Nobuaki; Castellano, Daniel; et al.
Summary: Background: The PROfound study showed significantly improved radiographical progression-free survival and overall survival in men with metastatic castration-resistant prostate cancer with alterations in homologous recombination repair genes and disease progression on a previous next-generation hormonal drug who received olaparib then those who received control. We aimed to assess pain and patient-centric health-related quality of life (HRQOL) measures in patients in the trial. Methods: In this open-label, randomised, phase 3 study, patients (aged ≥18 years) with metastatic castration-resistant prostate cancer and gene alterations to one of 15 genes ( BRCA1, BRCA2, or ATM [cohort A] and BRIP1, BARD1, CDK12, CHEK1, CHEK2, FANCL, PALB2, PPP2R2A, RAD51B, RAD51C, RAD51D, and RAD54L [cohort B]) and disease progression after a previous next-generation hormonal drug were randomly assigned (2:1) to receive olaparib tablets (300 mg orally twice daily) or a control drug (enzalutamide tablets [160 mg orally once daily] or abiraterone tablets [1000 mg orally once daily] plus prednisone tablets [5 mg orally twice daily]), stratified by previous taxane use and measurable disease. The primary endpoint (radiographical progression-free survival in cohort A) has been previously reported. The prespecified secondary endpoints reported here are on pain, HRQOL, symptomatic skeletal-related events, and time to first opiate use for cancer-related pain in cohort A. Pain was assessed with the Brief Pain Inventory-Short Form, and HRQOL was assessed with the Functional Assessment of Cancer Therapy-Prostate (FACT-P). All endpoints were analysed in patients in cohort A by modified intention-to-treat. The study is registered with ClinicalTrials.gov, NCT02987543 . Findings: Between Feb 6, 2017, and June 4, 2019, 245 patients were enrolled in cohort A and received study treatment (162 [66%] in the olaparib group and 83 [34%] in the control group). Median duration of follow-up at data cutoff in all patients was 6·2 months (IQR 2·2–10·4) for the olaparib group and 3·5 months (1·7–4·9) for the control group. In cohort A, median time to pain progression was significantly longer with olaparib than with control (median not reached [95% CI not reached–not reached] with olaparib vs 9·92 months [5·39–not reached] with control; HR 0·44 [95% CI 0·22–0·91]; p=0·019). Pain interference scores were also better in the olaparib group (difference in overall adjusted mean change from baseline score −0·85 [95% CI −1·31 to −0·39]; pnominal =0·0004). Median time to progression of pain severity was not reached in either group (95% CI not reached–not reached for both groups; HR 0·56 [95% CI 0·25–1·34]; pnominal =0·17). In patients who had not used opiates at baseline (113 in the olaparib group, 58 in the control group), median time to first opiate use for cancer-related pain was 18·0 months (95% CI 12·8–not reached) in the olaparib group versus 7·5 months (3·2–not reached) in the control group (HR 0·61; 95% CI 0·38–0·99; pnominal =0·044). The proportion of patients with clinically meaningful improvement in FACT-P total score during treatment was higher for the olaparib group than the control group: 15 (10%) of 152 evaluable patients had a response in the olaparib group compared with one (1%) of evaluable 77 patients in the control group (odds ratio 8·32 [95% CI 1·64–151·84]; pnominal =0·0065). Median time to first symptomatic skeletal-related event was not reached for either treatment group (olaparib group 95% CI not reached–not reached; control group 7·8–not reached; HR 0·37 [95% CI 0·20–0·70]; pnominal =0·0013). Interpretation: Olaparib was associated with reduced pain burden and better-preserved HRQOL compared with the two control drugs in men with metastatic castration-resistant prostate cancer and homologous recombination repair gene alterations who had disease progression after a previous next-generation hormonal drug. Our findings support the clinical benefit of improved radiographical progression-free survival and overall survival identified in PROfound. Funding: AstraZeneca and Merck Sharp & Dohme.